Earthquake mitigation in a high-risk zone: A mixed-methods analysis of knowledge, attitudes, and preparedness in East Kolaka, Indonesia - Ristiani Ristiani; Andi Ilmadana Manggabarani; Komang Opie Oktavia (Journal of Environment and Sustainability Education, 2026)
This study was motivated by the high earthquake hazard potential in East Kolaka Regency, Indonesia, associated with the activity of the Kolaka Fault, while community preparedness remains limited. The research aims to analyze community knowledge, attitudes, and preparedness toward earthquake disaster mitigation and to identify key factors influencing preparedness in high-risk areas. A sequential explanatory mixed-methods design was employed, consisting of a quantitative survey of 159 respondents in Lalolae District followed by qualitative interviews to deepen the interpretation of quantitative findings. Quantitative data were analyzed using validity and reliability tests, Pearson correlation, and multiple linear regression with IBM SPSS 25, while qualitative data were used to complement and explain statistical results. The findings indicate that community knowledge is at a moderate level, attitudes toward earthquake mitigation are generally positive, and preparedness remains moderate. Correlation analysis reveals a positive relationship between knowledge and attitudes. However, regression analysis shows that neither knowledge nor attitudes significantly predict preparedness, although knowledge demonstrates a relatively stronger association compared with attitudes. Qualitative findings suggest that direct disaster experience, institutional support, and participation in disaster training play a more substantial role in shaping community preparedness. These results highlight the importance of strengthening community-based disaster education, institutional engagement, and practical preparedness training to enhance disaster risk reduction (DRR) in earthquake-prone regions.